Power supply for internet of things (IoT) - Maung, Banyar (Nanyang Technological University, 2021)
With the growing population of modern society leaning toward digital-oriented lifestyle, Internet of things plays prominent role in our daily life. As Home appliances, telecommunication, transport, banking, and health care industry shift their directions toward digitalised environment, IoT offers us an opportunity to be more efficient in how we do things, saving us time. Smart wearable devices had been around for some time, mostly in the form of our day-to-day essentials and accessories that provide us useful information related to important vitals and alert us in the event of an emergency. The development of smart contact lens has a growing popularity, especially related to healthcare industry, due to its non-invasive method and accessibility to important biochemistry information within human tears that are closely related to that of the cardiovascular system. Although lithium-ion battery is widely used in various devices including initial smart contact lens due to its stable power supply, however safety and biocompatibility of its content become disadvantages to be used as power supply system of smart contact lens in long term consideration. It is still a major challenge for researchers to provide a sustainable and biosafe power supply system for IoT devices that will closely locate to human vital organs, including human eyes. The objective of this project is to fabricate biosafe battery, that can operate with electrolyte contents inside human eyes, which can be used as power supply system of smart contact lens and evaluate the performance of the fabricated battery.